Emergency front‐of‐neck airway by ENT surgeons and residents: A dutch national survey. Issue 5 (31st October 2018) - Bruijstens, Loes; Titulaer, Imke; Scheffer, Gert Jan; Steegers, Monique; van den Hoogen, Frank
Abstract : Objectives: ENT surgeons and anesthesiologists work closely together in managing challenging airway cases. Sharing knowledge, experiences, and expectations interdisciplinary is essential in order to facilitate decision‐making and adequate management in emergency front‐of‐neck airway cases. Methods: A survey was performed, to analyze level of experience, technique of preference, training, knowledge of material and protocols, and self‐efficacy scores of Dutch ENT surgeons and residents in performing an urgent or emergency front‐of‐neck airway. Results: Within one year (January 2014–2015), 25.7% of the 257 respondents had performed an urgent or emergency front‐of‐neck airway. Of all reported emergency front‐of‐neck airways (N = 30), 80% were managed by tracheotomy. In future emergency front‐of‐neck airway cases, 74% stated cricothyrotomy would be their technique of preference. The majority would choose an uncuffed large‐bore cannula technique. Post‐academic hands‐on training was attended by 42% of respondents. Self‐efficacy scores were highest for surgical tracheotomy, and higher when trained or experienced. In case of an emergency scenario, 8.6% would not perform a front‐of‐neck airway themselves. The main reasons for reluctance to start in general were lack of experience and lack of training. Reported items for improvement were mainly the development of a protocol and training. Conclusion: The chance of encountering an airway emergency scenario requiring front‐of‐neck airway is realistic. There is inconsistency between advised technique, technique of preference and technique actually performed by ENT surgeons. This study shows that there is both a need and desire for improvement in training and organization of care. Interdisciplinary guidelines and education is needed and could eventually safe lives. Level of evidence: 5